Labile and refractory fractions of sedimentary organic carbon off the Changjiang Estuary and its implications for sedimentary oxygen consumption - Cao, Yu; Huang, Hong; Zhao, Xu; Li, Jun; Wang, Teng; Lin, Jun; Zhu, Zhuo-Yi (Frontiers in Marine Science, 2023)
Estuarine and coastal area is dynamic zone for both marine carbon and oxygen cycles. There is limited evaluation of the labile and refractory fraction of sedimentary organic carbon and further a lack of attention to the corresponding potential in dissolved oxygen utilization. In this study, we collected sediment samples from the Changjiang estuary and adjacent coastal areas in the East China Sea in June 2019 to reveal the distribution, main controlling factor, and implications of four operational fractions of sediment organic carbon that range from labile to refraction. In the laboratory, we processed and defined the four operational fractions of sedimentary organic carbon, includes 1) pure water extractable carbon (WEC), 2) salt (K2SO4 solution) extractable carbon (SEC), 3) Microbial biomass carbon (MBC; chloroform extractable carbon), and 4) refractory organic carbon (ROC; the acid-processed fraction). We revealed that off the Changjiang Estuary, the bulk sedimentary organic carbon (SOC), WEC, SEC, MBC, and ROC were 9.43 ± 3.07 g/kg, 0.12 ± 0.10 g/kg, 0.16 ± 0.07 g/kg, 1.58 ± 0.45 g/kg, and 4.38 ± 1.95 g/kg, respectively. Sediment grain size played a vital role in constraining the LOC fractions, and samples from aquaculture areas showed extra-higher levels of LOC when compared to samples from the non-aquaculture area. The LOC and MBC fraction showed clear negative relation with dissolved oxygen (DO) in the near bottom waters under high DO background (DO > 5.5 mg/L), whereas in a low DO background (DO < 3-4 mg/L) no clear relation can be found. Based on our observed LOC content and DO concentration in the near bottom waters, the depth of hypoxia in the near bottom waters, which would be caused by a total decomposition of 4 mm of LOC in the top sediment, ranged between 0.3 m to 4.7 m with an average depth of 2 m. This value (2 m) means that sedimentary oxygen consumption would contribute 10% in the occurrence of hypoxia, with the rest contributing from water column respiration. Overall, we used the LOC fraction of sedimentary organic carbon to address the dissolved oxygen consumption in the near bottom waters and further study is needed to evaluate this approach.